Cor Triatriatum Sinister en un paciente canino- Reporte de un caso - Zavala N., Tania (2024)
Congenital heart diseases such as cor triatriatum sinister have a very low incidence in veterinary medicine and with very few cases in canines, unlike felines. It is reported the case of a three-year-old mixed-breed male dog that was presented to the clinic with progressive respiratory difficulty, and which had been diagnosed as a possible diaphragmatic hernia or pleural effusion. During the clinical evaluation, a heart murmur was detected, so after the stabilization of respiratory distress, echocardiography was performed among other tests, finding the following pathologies: cor triatriatum sinister, pulmonary stenosis, ventricular septal defect and tricuspid valve insufficiency; therefore. Medical treatment with diltiazem, sildenafil, and furosemide was instituted. Two months after diagnosis, the patient was stable according to the owners’ reports; however, they did not agree to perform more controls, so the patient’s follow-up was lost.